Gibson approach and surgical hip dislocation according to Ganz in the treatment of femoral head fractures - Domenico De Mauro (BMC, 2021)
Abstract Background The purpose of the study is to evaluate clinical and radiological outcomes in those patients with femoral head fracture, treated with open reduction and internal fixation through Gibson approach and Ganz flip trochanter osteotomy. The treatment of Pipkin fractures is very challenging, especially for small trauma centers, because of the unusual fracture patterns and high-level surgical skills required. Case presentation Between 2017 and 2020, nine cases of Pipkin fractures came to the Emergency Department at the Trauma Center of our Hospital in Rome. Inclusion criteria were the diagnosis of femoral head fracture, the open reduction and internal fixation as surgical choice and at least 24 months follow-up. Patients older than 65 years and those treated through total hip replacement or combined hip procedure (CHP) were excluded. Thus, five patients were included in our case series. The clinical outcome was evaluated according to Western Ontario and McMaster Universities Arthritis Index, Vail Hip score, modified Harris Hip score and Merle D’Aubignè Postel score. Radiographic assessment was scored according to Epstein-Thompson classification and heterotopic ossification was assessed through Brooker classification. The mean follow-up was 24 months (range 12-24). Average modified Harris Hip score was 92.1 points (range 75.9–100), and the average Vail score was 81.8 (range 55-95). WOMAC score was assessed in three different subscales, pain (A), stiffness (B) and physical condition (C), with the following results: 1.4 A (range 0-7), 1.2 B (range 0-6) and 6.4 C (range 0-22). Merle d’Aubignè Postel score resulted excellent for four patients and good for one patient. According to Epstein-Thompson score of the radiological outcome, four patients showed a good result and one a fair result. No mechanical or infective complications occurred in the five patients. Conclusions Gibson’s approach and surgical hip dislocation through Ganz trochanteric flip osteotomy allow a good exposure of the femoral head and acetabulum, giving us the possibility to perform an anatomical reduction of the fracture. In our case series, satisfactory clinical and radiological short-term results were obtained without significant complications.